Efektivitas promosi kesehatan dengan peer education pada kelompok dasawismadalam upaya penemuan tersangka pen derita tb paru - Elly Swandewi Murti , Yayi Suryo Prabandari, Bambang Sigit Riyanto (Berita Kedokteran Masyarakat (BKM), 2006)
Background: Lung tuberculosis is still a public health problem in Indonesia, and has a great social impact. Various control efforts have been implemented although they did not give expected result. The community showed that they did not understand appropriately the health information. The lack of community's knowledge regarding lung TB disease will influence community's behavior in controlling lung TB. Therefore, a more effective health promotion is needed. Dasawisma is one of community's participation which effected family. Health promotion with peer education method is expected could improve knowledge and behavior of group as dasawisma in controlling lung TB especially in the effort of finding lung TB patient.Objective: To find out the effectiveness of health promotion with peer education by improving knowledge and behavior of dasawisma group toward the effort of finding suspected lung TB.Method: This was a quasi experimental study with non-equivalent control group design. Participant of the research were 77 dasawisma mother that was selected purposively and divided into experiment (38) and control (39) groups. Data collection was conducted by using questionnaires of knowledge and behavior. Data analysis used paired t-test and independent t-lest with significance level of p=0,05.Result: The mother's knowledge and behavior of dasawisma mother who obtained health promotion through peer education were heigher than the mother's knowledge and behavior of dasawisma mother who did not receive the peer education in one month after the health promotion.Conclusion: Health promotion through peer education was more effective in improving knowledge and behavior of dasawisma mother in the effort of finding suspected lung TB patient compared with health promotion through large group health education in control group. Keywords: health promotion, peer education, tuberculosis